2006
DOI: 10.1124/jpet.106.114330
|View full text |Cite
|
Sign up to set email alerts
|

The Novel γ Secretase Inhibitor N-[cis-4-[(4-Chlorophenyl)sulfonyl]-4-(2,5-difluorophenyl)cyclohexyl]-1,1,1-trifluoromethanesulfonamide (MRK-560) Reduces Amyloid Plaque Deposition without Evidence of Notch-Related Pathology in the Tg2576 Mouse

Abstract: There is a substantial body of evidence indicating that ␤-amyloid peptides (A␤) are critical factors in the onset and development of Alzheimer's disease (AD). One strategy for combating AD is to reduce or eliminate the production of A␤ through inhibition of the ␥-secretase enzyme, which cleaves A␤ from the amyloid precursor protein (APP). We demonstrate here that chronic treatment for 3 months with 3 mg/kg of the potent, orally bioavailable and brain-penetrant ␥-secretase inhibitor N- [cis-4-[(4-chlorophenyl)s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 38 publications
(53 reference statements)
8
65
0
Order By: Relevance
“…In these cells, we found that MRK-560 inhibited all A␤ species analyzed with similar potency, and displayed approximately sixfold selectivity for A␤42 over NICD formation (Fig. 1A), which is in line with a previous report (Best et al, 2007). Next we addressed (BD8)).…”
Section: Mrk-560 Preferentially Inhibits Ps1-mediated Processing Of Asupporting
confidence: 75%
See 2 more Smart Citations
“…In these cells, we found that MRK-560 inhibited all A␤ species analyzed with similar potency, and displayed approximately sixfold selectivity for A␤42 over NICD formation (Fig. 1A), which is in line with a previous report (Best et al, 2007). Next we addressed (BD8)).…”
Section: Mrk-560 Preferentially Inhibits Ps1-mediated Processing Of Asupporting
confidence: 75%
“…In the context of AD, it is of particular interest that PS1 seems to catalyze the vast majority of CNS A␤ production (De Strooper et al, 1998;Borgegard et al, 2011) and that certain GSIs of the sulfonamide class appear to exhibit a preference for PS1 over PS2 ␥-secretase activities (Zhao et al, 2008;Borgegard et al, 2011), supporting the notion that development of ␥-secretase subcomplex selective GSIs may be feasible. In line with this, the sulfonamide GSI, MRK-560, inhibits A␤ production in an efficacious manner and reduces neural plaque formation without producing the Notchrelated off target effects observed in chronic studies in mice (Best et al, 2007). The mechanism by which Notch signaling is spared using MRK-560 has, however, not been unraveled, but is important to elucidate, as such information may guide development of the next generation GSIs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another study in 10-month-old Tg2576 mice receiving ibuprofen in the diet for 6 months (375 ppm) produced also similar results (Lim et al, 2000). Comparable effects were also recently described in 15-month-old Tg2576 mice after chronic treatment with the ␥-secretase inhibitor MRK-560 (3 mg/kg/day for 3 months; Best et al, 2007).…”
Section: Discussionsupporting
confidence: 61%
“…In addition, ␥-secretase inhibitors have been associated to alteration of lymphopoiesis (Wong et al, 2004) and atrophy of the thymus (Hadland et al, 2001). Toxicity of the ␥-secretase inhibitors may be linked to the specific chemical structure, since it has been shown that MRK-560, a potent APP and Notch cleavage inhibitor (IC 50 values ϭ 4.32 and 3.44 nM, respectively), administered for 3 months to aged Tg2576 mice significantly reduced brain A␤ pathology without causing histopathological changes in the ileum, spleen, or thymus (Best et al, 2007). Our present studies in HEK293swe cells indicated that CHF5074 concentrations inhibiting APP processing (5 M) do not affect Notch processing.…”
Section: Discussionmentioning
confidence: 99%